2020
DOI: 10.1002/jee.20311
|View full text |Cite
|
Sign up to set email alerts
|

Learning through making: The development of engineering discourse in an out‐of‐school maker club

Abstract: Background Learning to be an engineer means learning to participate in engineering discourse: the words, visuals, routines, and narratives through which engineers think and communicate. An important goal for engineering education is uncovering the processes by which young people take up and become fluent in engineering discourse, and how teachers and mentors can aid them in this process. Growing evidence suggests that participation in out‐of‐school maker activities—a class of informal design and build activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…This work is consistent with evidence that participation in co-curricular activities during high school increases the likelihood of pursuing higher education (Hossler and Stage 1992;Stage and Hossler 1989). In one recent study, Martin and Betser (2020) involved students in maker space (design and build) projects and found that this was effective means of stimulating student interest and skill in engineering design. The authors show that maker spaces can serve as a context for discourse around engineering education "including explorative imitation of engineering discourse routines within hands-on learning environments" (p. 194).…”
Section: School-based Determinantssupporting
confidence: 85%
“…This work is consistent with evidence that participation in co-curricular activities during high school increases the likelihood of pursuing higher education (Hossler and Stage 1992;Stage and Hossler 1989). In one recent study, Martin and Betser (2020) involved students in maker space (design and build) projects and found that this was effective means of stimulating student interest and skill in engineering design. The authors show that maker spaces can serve as a context for discourse around engineering education "including explorative imitation of engineering discourse routines within hands-on learning environments" (p. 194).…”
Section: School-based Determinantssupporting
confidence: 85%
“…Lots of new teaching technologies have been developed so far to tackle this problem. Learning through making, imitation of real life discourse is considered in the world pedagogy as the most successful alternative to traditional methods (Bitrian et al, 2020;Martin & Betser, 2020;Meij van der et al, 2020). Role play is one of the methods of teaching in team-based learning, proposed by American and Russian teachers: Johnson and Johnson (1999), Polat et al (2002).…”
Section: Introduction Of New Innovative Methods Of Teaching In Professional Training Is Closely Connectedmentioning
confidence: 99%
“…This example highlights how meaning can be shifted from the syntax of formalized knowledge to the embodiment of student‐designed engineering products. Martin and Betser's (2020) study of how youth in maker spaces developed engineering discourses highlighted the relationship between language and materials. Their analysis:
shows how the hands‐on, open‐ended, and youth‐driven nature of an activity was linked to the processes of learning.
…”
Section: Asset‐based Approaches For Engineering Education With Elsmentioning
confidence: 99%